The Role of Entrepreneurship Development for Women Welfare in Rural Area - Devita Riandika; Endang Mulyani (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2020)
Data from statistics Indonesia in 2017 indicates that entrepreneurship in Indonesia reaches 3.01% of the population, which is 225 million people. That number increased dramatically from 2014 which only amounted to 1.55%. Increasing the number of women entrepreneurs is still largely urbanized, whereas from rural communities the number is still limited. Women are expected to have the ability to develop their potential and improve the welfare of women in rural areas. Using Schumpeter’s theory which is then supported by hope theory explains why entrepreneurship is important for some women. The approach used in this research is to use a qualitative approach. The procedure in collecting data through the study of literature, namely in the form of activities to collect, review, and examine and search for documents or literature that can provide information needed in a research activity. This article investigates how and what rural women need to become entrepreneurs. Women in rural areas are more likely to be less involved in entrepreneurial activities and are less optimistic about the ability to engage in entrepreneurship education and the lack of confidence to start as an entrepreneur. Because in Schumpeter’s theory the most important factor that causes economic development is the process of innovation and the culprit, namely entrepreneurs. Community economic progress can only be applied with innovation by entrepreneurs. Whereas in the theory of hope, it is based on the interests of individuals who want to achieve maximum satisfaction and want to minimize dissatisfaction.